How to use technology effectively in post-compulsory education - Clarke, Alan 1952- (Routledge, 2011)
"The use of technology within the lifelong learning sector brings many benefits to learners, teachers and managers. Aimed at trainee and practising teachers, this book contains clear, practical guidance on how to use technology and e-learning effectively to enhance all aspects of teaching and learning in the post-compulsory sector. Alan Clarke explains the technologies that are available and how to use them from whiteboards and virtual learning environments to digital photographs, podcasts and e-portfolios. Each chapter is fully aligned with the new LLUK standards and includes teaching strategies, practical examples and case studies to show how these work in practice. Chapters include guidance on: - using e-portfolios, blogs and wikis to present and share information with colleagues and encourage reflection - motivating students and promoting collaboration using mobile devices, discussion groups and forums - how to use ICT to develop literacy and numeracy skills - ways to keep up to date with new and emerging technologies - using technology safely and securely. Including a wide range of activities, questions for reflective practice and links to further sources of information, this essential textbook will help trainee and practising teachers in post-compulsory education to understand the major ILT tools and use them confidently and effectively in their teaching"-- Provided by publisher
Literaturangaben
Keywords: Continuing education / Great Britain / Computer-assisted instruction; Digital communications / Study and teaching (Continuing education) / Great Britain; Information technology / Study and teaching (Continuing education) / Great Britain; Adult education / Great Britain / Computer-assisted instruction; Post-compulsory education / Great Britain / Computer-assisted instruction; Educational technology / Great Britain; Teaching / Great Britain / Aids and devices; EDUCATION / General; EDUCATION / Secondary; EDUCATION / Teaching Methods & Materials / General; Computerunterstützter Unterricht; Erwachsenenbildung; Großbritannien